Developing A Framework for EthicallyQuestionable Behavior in Consumption - fukukawa, Kyoko (2002)
In light of the growing interest in "ethically questionable" consumer behavior, this study explores possible explanations of the occurrence of such behaviour, and subsequently develops a theoretical framework. The study is based upon data collected from 72 U.K. consumers, acquired from a projective approach with scenarios. Taking the theory of planned behavior (TPB) as an initial analytical framework, attitude, social influence, opportunity(as perceived behavioral control in TPB) and perceived unfairnessare identified as the antecedents of ethically questionable behavior (EQB). Social influenceis extended to include a broader range of external influences from subjective norm in TPB. Opportunityis considered to represent an aspect of perceived behavioral control as available resource to engage in EQB. Perceived unfairnessis presented as an additional component and refers to the extent to which an actor is motivated to redress an imbalance that is perceived as unfair. Binary logistic models suggest that attitudeand social influenceconsistently impact on EQB, as TPB would predict. Analysis of variance suggests that perceived unfairnessand opportunity, though context specific, also show signs of significant influence on the acceptance and practice of this behavior. Additional to the construct of TPB, this study develops the dimension of perceived unfairnessin the context of EQB decision-making. In the context of TPB, it provides further insight into our understanding of EQB, helping to provide a theoretical framework.
Keywords: theory of planned behavior; Theoretical Development; perceived unfairness; Ethical decision making; consumer fraud; Consumer behavior